2017
DOI: 10.4102/sajems.v20i1.1655
|View full text |Cite
|
Sign up to set email alerts
|

Revenue, welfare and trade effects of European Union Free Trade Agreement on South Africa

Abstract: Background: Using the partial equilibrium WITS-SMART Simulation model to assess the impact of liberalisation under the Trade Development and Cooperation Agreement (TDCA) of a free trade area between the European Union and South Africa. The identification of the impact of such agreement allows for trade policy negotiation adjustment that can be beneficial for South Africa.Aim: The aim of the study is to estimate and discuss the impact of a Free Trade Agreement (FTA) with the European Union and South Africa. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
5
12
0
Order By: Relevance
“…This estimate is consistent with that of Guei et al (2017), who found that the economic welfare gain from the FTA between South Africa and the EU would be approximately US$134 million per year. The reform of the import administration level would yield the countries of SACU between 5.8 and 8.9 times as much economic gain (Table 4, column 7).…”
Section: Cost Of Waiting Timesupporting
confidence: 89%
See 2 more Smart Citations
“…This estimate is consistent with that of Guei et al (2017), who found that the economic welfare gain from the FTA between South Africa and the EU would be approximately US$134 million per year. The reform of the import administration level would yield the countries of SACU between 5.8 and 8.9 times as much economic gain (Table 4, column 7).…”
Section: Cost Of Waiting Timesupporting
confidence: 89%
“…A partial equilibrium model that has been applied in studies worldwide is the WITS-SMART model developed by the United Nations Conference on Trade and Development. It allows an approximate measure of the change in consumer surplus from a change in trade policies and has been used to analyse the welfare effects, due to trade, of the European FTA on South Africa (Guei, Mugano & Le Roux 2017). This model was built to help developing countries to assess quantitatively the implications of proposals for trade liberalisation through Multilateral Trade Negotiations (MTN), or the effect of changes in the Generalized System of Preference (GSP) schemes of developed countries.…”
Section: Model Specification and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Guei, Mugano, and Le Roux (2017) examine the revenue, welfare, and trade effects of European Union Free Trade Agreement on South Africa. They apply the WITS‐SMART 1 model on 2012 data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings indicate a total welfare effect valued at US$ 134 million coupled with US$ 1.036 billion of total trade effects (Guei, Mugano, & le Roux, 2017). Nevertheless, South Africa is likely to experience a revenue loss amounting to US$ 562 million (Guei et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%